HEMOPHAGOCYTIC SYNDROME IN EMERGENCY AND INTENSIVE PEDIATRICS - M.A. Maschan; N.V. Poltavets (Union of pediatricians of Russia, 2011)
Hemophagocytic lymphohistiocytosis, or hemophagocytic syndrome - is a serious disease, which is based on the disorder of regulation of the immune response that leads to an uncontrolled activation of cytotoxic T-lymphocytes and macrophages and, consequently, to a severe inflammatory organs damage. The cause of the disease is a genetic defect of regulatory mechanisms or acquired immune system dysfunction in severe infections, autoimmune diseases and certain tumors. Hemophagocytic syndrome - is a life-threatening condition. Early diagnostics and intensive care are the key to a cure and requires intensive medical and emergency pediatrics knowledge of the principles of diagnostics and treatment of this disease. This article summarizes the current understanding of biology and clinical hemophagocytic syndrome. The authors presented their data on the genetic structure of Russian patients cohort and provide recommendations on the choice of therapy.Key words: hemophagocytic syndrome, clinical course, diagnostics, children.